Altai zahchin’s khutagtyn datsan - G. Yadamjav (Nomadic Civilization: Historical Research, 2022)
The Zahchin Monastery is a continuation of the Oirad Dzungar Kingdom’s temples. The Oirad Monastery was first led by Baivgas and all the princes of Oirad took one of their boys to become a monk together with two hundred commoner boys in Tibet to the Dalai Lama and Banchin Bogd and became Buddhists. Among these beginners, the famous nobleman Ravjamba Zaya bandida Namkhaijamts, Achit tsorj, Darkhan tsorj, Darjaa gavj, Ravjamba Sodov, and many other wise men appeared in the Oirad region with the teachings of Bogd Zonkhov’s modern yellow hat religion, Dalai Lama, and Banchin bogd’s book of prophecies. «Oiradyn ikh khüree» was established and the religion was started. Ravjamba Zaya established «Oiradyn ikh khüree» and trained hundreds of disciples, the wise interpreters Agwaanloroijamts, Radnaabadraa, Uyzen nanso, Gunten gavj, Erh tsorj, Sharav gelen, Tarva gavj and Warrior nanso were the leaders. It is recorded in history that Ravjamba Zaya Bandida established the «Oiradyn ikh khüree», branched off from it and founded many monasteries and churches, and carried out major religious and cultural activities in Khalkh, Övörlögch, and Halimag.